World trigger. 13 - Ashihara, Daisuke, 1981-; Olsen, Lillian (San Francisco, CA : VIZ Media, LLC, 2016)
"Having fought their way into the top B-Rank group, Tamakoma-2 gets to battle it out with the big boys for a chance to make A-Rank. Can this squad of rookies win against seasoned veterans who are nicknamed the 'A-Rank reserves'?"--Back cover.
Translated from the Japanese.
Translation of: Warudo toriga.
"First published in Japan 2013 by Shueisha Inc., Tokyo"--Page facing t.p.
"This book reads from right to left"--Back cover.
"Parental advisory: World Trigger is rated T for Teen and is recommended for ages 13 and up. This v. contains fantasy violence"--Page facing t.p.
Young Adult
Keywords: Human-alien encounters -- Comic books, strips, etc. -- Fiction; Imaginary wars and battles -- Comic books, strips, etc. -- Fiction; Space warfare -- Comic books, strips, etc. -- Fiction; Science fiction comics; Graphic novels